A Short Islamic Lecture Video Transforming Islamic Service Among Nursing Students in Hospitals - Nugroho, Fajar Agung; Nugroho, Irmawan Andri; Handoko, Puji (GLOBAL HEALTH SCIENCE GROUP, 2024)
Clinical practice in hospitals is an essential part of nursing education, where students apply the nursing theory they have learned in college. Nurses are among the most crucial professionals in providing services in hospitals. The existing phenomenon shows that there are still many patient complaints about unsatisfactory service quality. Purpose: To analyze the effect of the CEKAT BAIK Lecture Program in the application of Islamic services among hospitalized patientsMethod: A pre-experimental research method with a one-shot case study design. The study population was 100 hospitalized patients, and the sample amounted to 98 respondents using a purposive sampling technique. The research instrument was a questionnaire that underwent construct validity testing using Pearson’s product-moment correlation and content validity testing in collaboration with experts in religion, nursing, and language, as well as reliability testing in the inpatient ward of a private hospital. The data analysis technique uses One-Way ANOVA. Results: The calculated F value of 35.86 and the F table value is 3.091, so the calculated F value <F table (35.86 <3.091) means that there is a good linear effect on Islamic services.Conclusion: It is anticipated that implementing an Islamic service model as an alternative for patient care and nursing will be guided by Islamic principles, incorporating holistic approaches through sociocultural and spiritual services.